Range identification for a perspective dynamic system with a single homogeneous observation - Ma, Lili; Chen, YangQuan; Moore, Kevin L. (Zielona Góra: Uniwersytet Zielonogórski)
Perspective problems arise in machine vision when using a camera to observe the scene. Essential problems include the identification of unknown states and/or unknown parameters from perspective observations. Range identification is used to estimate the states/positions of a moving object with known motion parameters.
Keywords: range identification; perspective dynamic systems; nonlinear observer